Biodiversity of Mushrooms in Conservative Forest in Dansai District of Loei Province, Thailand - Rachadaporn Benchawattananon (Tropical Life Sciences Research, 2016)
Dansai District is located in Loei Province, Northeast Thailand, rich in natural resources and composes of many kinds of forests, such as evergreen forests and mixed-deciduous forests. The objectives of the study are to determine the diversity of mushrooms and investigate the values of the forest influencing the community way of life and exploration of problems and guidelines for developing the forest along with sufficiency economy theory. The study includes compilation of data from past studies, semi-structured interview with the local communities and discussion with focus group. The survey was done once a month during the rainy season from May to August in 2012 and 2013. The results of the survey revealed 56 species belonging to 26 families, 38 genera. A total of 52 mushroom species belong to Basidiomycota, while 4 species belong to Ascomycota. The community forest remains fertile due to the conservation effort by the community leaders and a group of villagers. A community forestry board were set up to conserve the forest and proposed to the government at Dansai Vocational Community College to officially declare the forest as a formal community forest. The conservation management relied upon the kinship relations, seniority, and religious belief along with the enforcing authorities. If an encroacher is found, he would be fined according to the regulations and defamed publicly. However, encroachment still exists. In general, community forest is valuable and directly affected the villagers’ ways of life in which they could generate income from the forest, particularly reducing the daily expenses and promoting their socio-cultural perspective.